2019
DOI: 10.3389/fpsyg.2019.00718
|View full text |Cite
|
Sign up to set email alerts
|

Environment-Specific vs. General Knowledge and Their Role in Pro-environmental Behavior

Abstract: Environmental knowledge has been established as a behavior-distal, but necessary antecedent of pro-environmental behavior. The magnitude of its effect is difficult to estimate due to methodological deficits and variability of measures proposed in the literature. This paper addresses these methodological issues with an updated, comprehensive and objective test of environmental knowledge spanning a broad variety of current environment related topics. In a multivariate study ( n = 214), lat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
88
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(118 citation statements)
references
References 77 publications
(114 reference statements)
5
88
1
Order By: Relevance
“…However, students' engagement in direct impact PEBs (e.g., waster separation, energy-saving behavior, and reuse and recycling behaviors) cannot be enhanced by only students' participation in an environmental course. As found in the study of Geiger et al [75], though people had a high level of both general and environmental knowledge such as knowledge of ecological systems, sustainability issues, effective actions and environmental situations, their engagement in PEBs was merely average. Several studies indicated the influence of other factors on PEBs engagement.…”
Section: Discussionmentioning
confidence: 86%
“…However, students' engagement in direct impact PEBs (e.g., waster separation, energy-saving behavior, and reuse and recycling behaviors) cannot be enhanced by only students' participation in an environmental course. As found in the study of Geiger et al [75], though people had a high level of both general and environmental knowledge such as knowledge of ecological systems, sustainability issues, effective actions and environmental situations, their engagement in PEBs was merely average. Several studies indicated the influence of other factors on PEBs engagement.…”
Section: Discussionmentioning
confidence: 86%
“…It is furthermore important to distinguish between objective (or actual) and subjective (or self-rated) assessments of knowledge (Shi et al 2016). Whereas measures of objective knowledge employ knowledge questions (true/false or multiple choice), subjective knowledge represents a self-assessment of, for example, familiarity, awareness, or level of knowledge (Steele et al 2006;Marzano et al 2017), thus resembling the concept of self-efficacy, i.e., the belief in one's own ability to act (Bandura 1977) (Geiger et al 2019a).…”
Section: Knowledge and Forest Managementmentioning
confidence: 99%
“…Possibly as a result of this, evidence about the relationship between environmental knowledge and pro-environmental behaviour is highly varied. Many studies have found a direct positive relationship [11,[47][48][49][50][51], but others have only found indirect effects. Most notably, meta-analyses [52,53] support an indirect positive relationship of environmental knowledge and pro-environmental behaviour, mediated by behavioural intentions, normative variables and guilt.…”
Section: Environmental Knowledge and Ecological Footprintmentioning
confidence: 99%